Interpreter Services in a General Health Setting in Western Australia: A Retrospective Study - Kwan, Michelle; Jeemi, Zakia; Norman, Richard; Dantas, Jaya A R (Curtin University, 2020)
Migration patterns have rapidly changed in Australia which have contributed to an increasingly culturally and linguistically diverse society. This has brought new opportunities and challenges in the healthcare sector to address the different language needs of the culturally and linguistically diverse (CaLD) populations. A key strategy is the provision of interpreter services to bridge the language gap and assist patients and healthcare providers in clinical encounters.